DIGITALISASI PUBLIC SERVICE DALAM IMPLEMENTASI APLIKASI SRIKANDI DENGAN PENDEKATAN HOLISTIK - Enza Resdiana; Nur Inna Alfiyah; Dwi Listia Rika; Tini Tini; Very Ardianingsih (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2026)
The SRIKANDI application is part of the acceleration of the Electronic-Based Government System (SPBE), in line with Presidential Regulation No. 95/2018. This regulation encourages local governments to strengthen transparency, accountability, and efficiency of public services through the digitization of archives and correspondence. However, in Sumenep Regency, the implementation of this application has not been fully used by local governments down to village governments. The suboptimal use of this application requires an accurate analysis to identify the obstacles that occurred during the application's socialization within the government. By using a holistic approach, this study will thoroughly examine the integration of various elements—technology, human resources, regulations, and organizational culture—to create an efficient, inclusive, and sustainable service system with an emphasis on efforts to ensure a comprehensive digital transformation in Sumenep Regency. The purpose of this study is to identify the strengths and weaknesses in the adoption of innovative technology with a holistic approach that involves how technology, infrastructure, human resources, work culture, organization, regulations, and processes influence the implementation of the SRIKANDI application in the Sumenep Regency government. The method used in this research uses descriptive explanatory with the focus of this research theory based on Goldstein's holistic approach. This theory underlies the understanding that for successful public digitalization (such as the Srikandi application), the government must view the system as a whole: humans, technology, processes, regulations, and the environment interact continuously, adapt, and develop together.